2020
DOI: 10.1111/hiv.12980
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive ageing is premature among a community sample of optimally treated people living with HIV

Abstract: Objectives Evidence of premature cognitive ageing amongst people living with HIV (PLHIV) remains controversial due to previous research limitations including underpowered studies, samples with suboptimal antiretroviral access, varying rate of virological control, high rate of AIDS, over‐representation of non‐community samples, and inclusion of inappropriate controls. The current study addresses these limitations, while also considering mental health and non‐HIV comorbidity burden to determine whether PLHIV sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
1
8
0
1
Order By: Relevance
“…Our finding that ART-treated PWH had higher incidence and prevalence of dementia than PWoH across all time periods is consistent with growing evidence that cognitive aging may be premature and/or accelerated among PWH [35][36][37][38][39][40][41][42]. These results also align with a recent study within an independent KP Northern Californian cohort from 2013 to 2019, which found elevated dementia risk among ART-treated PWH compared with demographically matched uninfected PWoH, even after controlling for traditional dementia risk factors [27].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that ART-treated PWH had higher incidence and prevalence of dementia than PWoH across all time periods is consistent with growing evidence that cognitive aging may be premature and/or accelerated among PWH [35][36][37][38][39][40][41][42]. These results also align with a recent study within an independent KP Northern Californian cohort from 2013 to 2019, which found elevated dementia risk among ART-treated PWH compared with demographically matched uninfected PWoH, even after controlling for traditional dementia risk factors [27].…”
Section: Discussionsupporting
confidence: 91%
“…HAND is an umbrella term which encompasses diseases of growing severity including asymptomatic neurocognitive impairment (ANI), mild neurocognitive disorder (MND) and HIV-associated dementia (HAD). Whilst the incidence of the most severe forms has fallen, prevalence of milder neurocognitive impairments remains comparable to the pre-ART era [58].…”
Section: Hiv and The Central Nervous Systemmentioning
confidence: 99%
“…At baseline (2011–2012), their neurocognitive functioning, mental health and HIV, and general health were assessed. The baseline data have been published (Aung et al 2021b ; Bloch et al 2016 ; Kamminga et al 2017 ). We observed that premature aging among PLHIV compared to HIV-negative controls was associated with worse neurocognitive functioning (Aung et al 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…The baseline data have been published (Aung et al 2021b ; Bloch et al 2016 ; Kamminga et al 2017 ). We observed that premature aging among PLHIV compared to HIV-negative controls was associated with worse neurocognitive functioning (Aung et al 2021b ). Thus, 10 years later, we had the opportunity to determine the burden of ARC including non-HIV age-related neurological disorders.…”
Section: Introductionmentioning
confidence: 99%